The impact of mitochondrial functionality on oxidative stress in human cancer cells: a Systematic Review - Khulud M Alshehri (International Journal of Medical Toxicology and Legal Medicine, 2024)
This systematic review aimed to evaluate research done on the impact of mitochondrial functionality on oxidative stress in human cancer cells with three objectives. The objectives were related to observing temporal trends in research on this topic, evaluating the cause of oxidative stress in human cancer cells and reviewing the progress in research on interventions and therapies. Papers were identified from Google Scholar using search terms for each objective. The identified papers were screened through the PRISMA flow process to obtain 10 papers each for each objective. This review showed that the number of papers increased by the year and the USA and China dominated in this respect. Oxidative stress due to mitochondrial malfunctions and certain allied factors were identified as the main causes of human cancer. Many drugs are used for cancer therapy, but without adequate evidence and involve many risks. Many new drugs are at various trial stages. Nano-technology-based targeted drug delivery systems promise to be a promising method of effective cancer therapy with minimum risk. This may be a future research area along with the development of novel drugs. The limitations of using a single database, papers in English only and limiting the number of papers to 10 for each objective are acknowledged.